Historical record about the state schools of professional education in Ceará - Souza , Maria Francimar Teles de; Azevedo , Luciana Cavalcanti de (Seven Editora, 2023)
The professional education network in the State of Ceará was implemented in 2008 through the Department of Education with the project of implementation of the State Schools of Professional Education, through State Law No. 14,273 of 2008. This article seeks to describe the organizational and functioning characteristics of these institutions in the State of Ceará. It is a work that is part of the Dissertation of the Master's Program in Professional and Technological Education in National Network – ProfEPT, in progress at the Federal Institute of Science and Technology of the Sertão Pernambucano – IFSertãoPE. The data presented here were collected through bibliographical and documentary research, showing a little of the history, legislation, dynamics of operation and objectives of these educational institutions, which seek to carry out a work aimed at the integral formation of students with a view to developing a meaningful learning, capable of valuing culture and work,  as well as a global understanding of production processes and scientific and technological knowledge. They are institutions that work in full shift with articulation between the disciplines of the technical base – professional axis and common base – disciplines of basic education. They use a management philosophy anchored in the Socio-Educational Business Technology - TESE, which served as the basis for the definition of the basic principles of the work, whose premises have as representative landmarks the connection between objectives, priorities and results expected by all members of the educational institution and the community. DOI:https://doi.org/10.56238/ptoketheeducati-065